The efficiency of Leguminoceae Production Grains Plus Maize as A Feeding on Growth Phase of Local Swine (Potamochoerus porcus) in Timor-Leste - A. Afonso; E. S. D. C. Cruz; I. S. Pereira; M. D. C. Napoleão; C. N. Nabais (Universitas Andalas, 2022)
In Timor Leste, swine Farmers did not yet use legume production grains to maintain feed swine performance and respond to market demand. The research aims to evaluate the Efficiency of Leguminoceae Production grains Plus Maize in feeding on the Growth Phase of Local Swine in Timor Leste. This research used Latin Square Design with four rows and four columns employed. The swine feeding has 4 treatments such as R1 (corn 50% + mungbean 15% + soybean 20% + common bean 15%), R2 (corn 40% + mungbean 20% + soybean 15% + common bean 25%), R3 (corn 40% + mungbean 20% + soybean 20% + common bean 20%), R4 (corn 50% + mungbean 10% + soybean 15% + common bean 25%). This research showed that Swine that consumed R2 rates were very good compared to other feedings for Swine. Look at the performance of the Swine with an increase in body weight of 31.16kg and body length of 72.75cm in the grower phase. All data were analyzed by ANOVA Latin Square Design, and Least Significance Difference (LSD) was conducted when the means were significantly different (p<0.05).